2020
DOI: 10.1155/2020/8844293
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Injection to Enhance Hydraulic Fracturing Efficiency: Insights from Laboratory Experiments

Abstract: In hydraulic fracturing applications, there is substantial interest to reduce the formation breakdown pressure. Previous research results show that the cyclic injection method can be used to reduce that pressure. In this study, we conducted laboratory hydraulic fracturing experiments to apply cyclic injection to reduce the breakdown pressures of very tight and strong sandstones. Experimental results show that using cyclic injection the average breakdown pressure was reduced by 18.9% in very tight sandstones an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…In ultra-tight concrete, the reduction percentage is higher (25%) compared with in low-and medium-strength cement blocks (15%) 55 . This finding on concrete is in line with experiments on Xujiahe sandstone 56 . These authors reported smaller breakdown-pressure reduction (7%) in high-porosity samples (13%) as compared with a larger reduction (19%) in low-porosity sandstone (1%).…”
Section: Discussion Of Field Application and Evidencesupporting
confidence: 91%
“…In ultra-tight concrete, the reduction percentage is higher (25%) compared with in low-and medium-strength cement blocks (15%) 55 . This finding on concrete is in line with experiments on Xujiahe sandstone 56 . These authors reported smaller breakdown-pressure reduction (7%) in high-porosity samples (13%) as compared with a larger reduction (19%) in low-porosity sandstone (1%).…”
Section: Discussion Of Field Application and Evidencesupporting
confidence: 91%
“…First, the FBP is slightly higher using the CPI scheme, between 0.5 and 1 MPa, regardless of rock fabric. Although this agrees with the laboratory experiments of Zhuang et al [53], this is in contrast to laboratory studies such as Patel et al [38] and Kang et al [25] where FBP drops with number of injection cycles. Considering the laboratory tests of Zhuang et al [53], there are mainly two reasons for the variation of FBP.…”
Section: Comparison Of Hydro-mechanical Indicators Due To Different I...supporting
confidence: 85%